Cetuximab‐conjugated nanodiamonds drug delivery system for enhanced targeting therapy and 3D Raman imaging. Issue 12 (21st June 2017) - Li, Dandan; Chen, Xin; Wang, Hong; Liu, Jie; Zheng, Meiling; Fu, Yang; Yu, Yuan; Zhi, Jinfang
Abstract: In this study, a multicomponent nanodiamonds (NDs)‐based targeting drug delivery system, cetuximab‐NDs‐cisplatin bioconjugate, combining both specific targeting and enhanced therapeutic efficacy capabilities, is developed and characterized. The specific targeting ability of cetuximab‐NDs‐cisplatin system on human liver hepatocellular carcinoma (HepG2) cells is evaluated through epidermal growth factor receptor (EGFR) blocking experiments, since EGFR is over‐expressed on HepG2 cell membrane. Besides, cytotoxic evaluation confirms that cetuximab‐NDs‐cisplatin system could significantly inhibit the growth of HepG2 cells, and the therapeutic activity of this system is proven to be better than that of both nonspecific NDs‐cisplatin conjugate and specific EGF‐NDs‐cisplatin conjugate. Furthermore, a 3‐dimensional (3D) Raman imaging technique is utilized to visualize the targeting efficacy and enhanced internalization of cetuximab‐NDs‐cisplatin system in HepG2 cells, using the NDs existing in the bioconjugate as Raman probes, based on the characteristic Raman signal of NDs at 1332 cm −1 . These advantageous properties of cetuximab‐NDs‐cisplatin system propose a prospective imaging and treatment tool for further diagnostic and therapeutic purposes. Abstract : Cetuximab‐nanodiamonds (NDs)‐cisplatin targeting drug delivery system is developed in this work, which combines specific targeting and enhanced therapeutic efficacy capabilities, incomparison with nonspecific NDs‐cisplatin conjugate and specific EGF‐NDs‐cisplatin bioconjugate. Besides, the three‐dimensional Raman imaging technique is utilized to visualize the performance of NDs‐based drug delivery system in cancer cell targeting and internalization. These advantageous properties of cetuximab‐NDs‐cisplatin propose a promising treatment and imaging tool for further clinical application.